Inverse optimization design of sugarcane seeding mechanism based on approximate multi-position and posture - Chen, Qingli; Liu, Jiaodi; Xu, Hongzhen; Hua, Yong; Wu, Xiaoman (International Journal of Agricultural and Biological Engineering, 2025)
The current sugarcane seeding mechanism is unable to accomplish complex seeding movement trajectories and postures, thus failing to enable the cane seed to enter the seed trench in a stable posture, resulting in a high rate of collapse and a low survival rate. A second-order non-circular planetary gear system pendulum-type seeding mechanism is adopted to realize the complex motion of seeding arm taking seeds in an orderly manner, transporting seeds stably, and sowing seeds in a fixed posture. Constraining the position and posture of the end point of the seeding arm, based on the principle of second-order center distance invariance in the motion process of the planetary gear train, the inverse optimization design model of approximate multi-positional posture is established, and the initial optimal parameters of the double-motion point of the mechanism are solved by genetic algorithm. The second-order non-circular gear ratios are assigned according to the kinematic characteristics of the mechanism in order to design all the non-circular gear pitch curves and model their convexity calculations. In order to avoid the influence on the preset position and posture, the position of the corresponding relative angular displacement fitting point of the adjustable trajectory segment on the closed motion trajectory is taken as the optimization variable, and the convexity optimization model of the second-order non-circular gear pitch curve is established. A set of non-circular gear pitch curves with better roundness is obtained by NSGA II multi-objective optimization algorithm combined with entropy weight TOPSIS game theory. The simulation results show that the motion trajectory posture of the virtual prototype is basically consistent with the theoretical model, which meets the agronomic requirements of sugarcane seeding and verifies the feasibility of the mechanism design.Keywords: sugarcane seeding, inverse optimization design, second-order non-circular planetary gear train, non-circular gear pitch curve convexityDOI: 10.25165/j.ijabe.20251803.8797Citation: Chen Q L, Liu J D, Xu H Z, Hua Y, Wu X M. Inverse optimization design of sugarcane seeding mechanism based on approximate multi-position and posture. Int J Agric & Biol Eng, 2025; 18(3): 73–81.